2012
DOI: 10.1111/j.1440-1819.2012.02348.x
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary outcome study on assertive community treatment in Japan

Abstract: Aims:  The beneficial effects of assertive community treatment (ACT), which has been widely acclaimed as being successful in several foreign countries, must also be objectively evaluated with respect to the transition from inpatient to community‐based mental health treatment in Japan. This was the first study that examined effects of the ACT program in Japan using pre/post design data of the pilot trial of the ACT program in Japan project. Methods:  The study included 41 subjects hospitalized at Kohnodai Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Similarly, controlled trials in the U.S., particularly in good service areas, have not consistently found better outcomes for ACT in recent years, as the U.S. has continued to sharply reduce the rate of hospitalization admissions and length of hospital stays. Internationally, ACT continues to be an attractive service model option in some nations, such as Japan , with poorly developed community mental health services and routine use of long‐term hospitalizations.…”
Section: Absorption In Standard Servicesmentioning
confidence: 99%
“…Similarly, controlled trials in the U.S., particularly in good service areas, have not consistently found better outcomes for ACT in recent years, as the U.S. has continued to sharply reduce the rate of hospitalization admissions and length of hospital stays. Internationally, ACT continues to be an attractive service model option in some nations, such as Japan , with poorly developed community mental health services and routine use of long‐term hospitalizations.…”
Section: Absorption In Standard Servicesmentioning
confidence: 99%
“…Single-site studies on the effectiveness of ACT tend to have small sample sizes (range 41 to 64) [6,7,11]. The reason for this may vary from country to country, but in a developing country such as RSA, limited human and financial resources are the main drivers behind this.…”
Section: Resultsmentioning
confidence: 99%
“…Though considered an expensive intervention, the costs were justified under the premise that inpatient costs were generally much higher. The approach has been well researched and tested over the last twenty years, with many countries reporting on a range of outcomes, such as readmission rates, patient satisfaction, degrees of symptomatology and social functioning [4,3,2,7]. Initial studies from particularly the US and Australia, reported positive outcomes in most of these areas, which prompted UK decision makers to launch 300 Assertive Outreach teams nationwide [1-3].…”
Section: Introductionmentioning
confidence: 99%
“…Japan had several ACT teams and research that showed some desirable outcomes. Nishio et al () found that individuals could live longer in the community without a worsening of symptoms or decreasing social function. Another study reported that an ACT group had a reduction of inpatient days and better client satisfaction than a non‐ACT group (Ito et al , ).…”
Section: Introductionmentioning
confidence: 99%